Role of Rare Species on Phytoplankton Size–Abundance Relationships and Size Structure across Different Biogeographical Areas - Maira Laraib; Jessica Titocci; Antonia Giannakourou; Sofia Reizopoulou; Alberto Basset (Diversity, 2024)
Phytoplankton guilds are commonly characterised by dominance effects, while the main contribution to biological diversity is given by rare species. Here, we analysed the influence of rare species on taxonomic and functional diversity, which is described by taxa richness and composition, cell size, and size–abundance relationships in phytoplankton guilds. We explore these relationships at global and regional scales by analysing phytoplankton guilds from five biogeographical regions: the Northern Atlantic Ocean (Scotland), the South-Western Atlantic Ocean (Brazil), the South-Western Pacific Ocean (Australia), the Indo-Pacific Ocean (Maldives), and the Mediterranean Sea (Greece and Turkey). We have comparatively analysed the phytoplankton taxonomic diversity of the whole dataset and with the datasets obtained by progressively subtracting taxa occurring in the last 1%, 5%, 10%, and 25% of both numerical abundance and overall biomass. Globally, 306 taxa were identified across five ecoregions with only 27 taxa accounting for 75% of overall numerical abundance and biomass; almost 50% of taxa were lost on every step. The removal of 1% of most rare taxa significantly affected the phytoplankton size–abundance relationships and body-size structure, strongly impacting on small taxa. The progressive removal of additional rare taxa did not further affect phytoplankton size–abundance relationships and size structure.